Analisis Hukum Surat Pelepasan Hak Atas Tanah Adat (Dati) Di Kota Ambon - Desy Kosita Hallauw; Jenny Kristiana Matuankotta; Novyta Uktolseja (Faculty of Law, Universitas Pattimura, 2020)
Relinquishment of land rights is the relinquishment of legal relations between the holders of land rights and the land under their control by providing compensation on the basis of deliberation. Letter of Waiver of rights is evidence that is made with the aim of releasing land rights. A letter of release of customary land rights (dati) is applied in the same way as the release of land rights in general, as enforced in accordance with Government Regulation No. 24 of 1997 concerning Land Registration. The process of registering customary land rights (dati) is based on the release of customary rights (dati) issued by the customary land owner (dati) as the basis for rights. So based on the release of land rights, it can be registered at the Ambon City Land Office to obtain proof of land ownership or certificates. The letter of release of customary land rights (dati) issued by the customary State Government in Ambon City is binding as long as it is carried out based on applicable customary law and can be proven the basis of ownership rights to customary land (dati) from the customary land owner (dati) that issues the release letter the land rights. However, as long as it cannot be proven valid, the letter of release of land rights does not have binding power, thus the release of the customary land rights (dati) becomes invalid and the certificate can be canceled.